An Analysis of Hyperbole in The Novel "Remember Me" by Sophie Kinsella - Dewi, Ni Luh Putu Septiadewi; Desak Putu Eka Pratiwi (SPHOTA: Jurnal Linguistik dan Sastra, 2023)
The research aims to identify types of figurative language, especially hyperbole, and analyze the meanings. The data are taken from the novel entitled "Remember Me” by Sophie Kinsella. The method used in collecting the data was the qualitative method. First, reading the novel repeatedly and understanding the novel "Remember Me" by Sophie Kinsella. Second, note-taking to find out a figurative language is used in the novel "Remember Me” by Sophie Kinsella. Third, analyzing the data. The writer analyzed the data descriptively by using the qualitative method. Two theories are used in this analyzing the data, the first theory is proposed by Perrine (1977) which is used to find out the types of figurative language used in the novel "Remember Me" by Sophie Kinsella. The second theory is delivered by Leech (1981) which is used to find out the meaning of the figurative language used in the novel "Remember Me" by Sophie Kinsella. The finding shows that the whole of the figurative language has connotative meaning. The writer found ten types of hyperbole used in the novel “Remember Me”. This research is expected to contribute as a medium for learning language styles because there are so many enthusiasts of novels that it makes more and more people like to read novels. After all, novels will be more interesting and have high scores in language style.